Anthropology and demography - Bošković Aleksandar (Stanovništvo)
The paper presents an outline of the relationship between anthropology and demography, sometimes depicted as "long, tortured, often ambivalent, and sometimes passionate." Although early anthropologists (primarily British social anthropologists) routinely made use of demographic data, especially in their studies of kinship, the two disciplines gradually drifted away from each other. The re-approachment took place from 1960s, and the last fifteen years saw more intensive cooperation and more insights about possible mutual benefits that could be achieved through combining of methodologies and revision of some theoretical assumptions, primarily through anthropological demography. As summarized by Laura Bernardi and Inge Hutter, "Anthropological demography is a specialty within demography that uses anthropological theory and methods to provide a better understanding of demographic phenomena in current and past populations. Its genesis and ongoing growth lies at the intersection of demography and socio-cultural anthropology and with their efforts to understand population processes: mainly fertility, migration, and mortality. Both disciplines share a common research subject, namely human populations, and they focus on mutually complementary aspects" (2007: 541). In the first part of the paper, the author presents some general considerations, like the one that "demography is one of the best understood and predictable parts of human behavior, even if demographers still find themselves unable to predict accurately when parameters will change in interesting ways, such as the ′the baby boom′ or the shift to later childbeanng in the 1970s and 1980s North America" (Howell, 1986: 219). Nancy Howell also noted the importance of demographic anthropology, because, in her words "if we knew, reliably, the birth and death probability schedules of particular populations, we would know a great deal about their size, age composition, growth rate. And with just a little more information we would know a great deal more such as household and family composition, economic organization, social problems, and something of the political structure. It we knew the schedules for populations in general and could correlate the schedules with the causes, genetic or environmental, that produce them, we would know a great deal about the possible range of human social structure" (Howell, 1986: 219). In the second part of the paper, the author discusses several examples of interplay between anthropology and demography. One of them is Patrick Heady′s study of the shift in ritual patterns, which combines elements of some "classical" anthropological topics (Mauss’s theory of gift exchange and Lévi-Strauss′s concept of kinship) with his own field research in the Carnian Alps. "By marrying and raising children, parents participate in a system of gift-exchange in which the gifts in question are human lives, and the parties to the exchange are the kinship groups recognized in the society concerned. Fertility reflects the attitudes of prospective parents to their place in the existing system of reproductive exchange, and the relationships of cooperation and authority which it implies - as well as their confidence in the system’s continuing viability. It is shown that this view is compatible with earlier ideas about self-regulating population systems - and that changing economic circumstances are an important source of discrepancy between existing exchange systems and the attitudes and expectations of prospective parents" (Heady, 2007: 465). The paper concludes with the discussion of the directions in which relationship between these two disciplines can proceed. Some of the epistemological issues are mentioned, as well as a need to apply different theoretical perspectives to better understand demographic behavior (especially in Europe) and to better understand certain cultural components that shape this behavior. In order to achieve this, most of the scholars whose works are discussed in this paper emphasize "the need for a holistic approach to data collection and the added value of triangulating quantitative and qualitative analyses" (Bernardi, Hutter, 2007: 541). [Projekat Ministarstva nauke Republike Srbije, br. 47010: Društvene transformacije u procesu evropskih integracija - multidisciplinarni pristup]